Social Interaction In Inclusive Learning at Junior High School - Anjar Kusuma Dewi; Muhammad Nur Ali; Hasan Muhammad (LPPM Universitas PGRI Sumatera Barat, 2023)
This study explored the dynamics of symbolic interaction within inclusive classrooms at SMP Negeri 1 Palu, demonstrating that social interaction serves as a foundational mechanism shaping both pedagogical processes and the meaning of inclusion itself. The research revealed two predominant patterns—peer support interaction, emerging spontaneously through academic assistance, emotional support, and social advocacy, and dialogic interaction with teachers, functioning as reciprocal communication that enables inclusive students to construct meaning and negotiate their identities. These patterns operate across four critical dimensions: identity formation through social mirroring, emotional regulation through socioemotional support, cognitive mediation through scaffolding, and social transmission of knowledge through observational learning. However, the study also uncovered significant constraints—peer support proves stronger in social than academic contexts, dialogic interaction requires resources often unavailable, and students with severe communication barriers may remain marginalized despite institutional commitment. These findings shift analytical focus from policy frameworks to lived relational dynamics, demonstrating that inclusion transcends physical presence to require authentic social spaces where equality and acceptance are continuously negotiated. As Indonesia strengthens its commitment to inclusive education, lasting progress demands sustained attention to the quality and responsiveness of everyday classroom interactions—for it is within these interactions that inclusion is ultimately made, negotiated, and lived, compelling us to ask whether educational systems are truly prepared to prioritize and sustain the relational conditions that make authentic inclusion possible.